2012
DOI: 10.1542/peds.2012-1379
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Neurocardiogenic Syncope in Children: A 2-Year Prospective Study

Abstract: Depressive symptomatology is common in pediatric patients with NCS. Our findings call for additional investigation in larger controlled clinical interventional studies that will enhance understanding of the possible pathophysiological association between depressive symptomatology and NCS in pediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Although, other studies [6,7] evidenced a good prognosis in patients with NCS, we experienced a great impact on quality of life in patients and their families. In this group of patients we reported a major frequency of somatic and thought problems as skin problems, vomit, stomach problems, sleep problems and unusual thoughts compared with healthy subjects and of emotional problems as anxiety, depressive withdrawal and somatic complaints.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Although, other studies [6,7] evidenced a good prognosis in patients with NCS, we experienced a great impact on quality of life in patients and their families. In this group of patients we reported a major frequency of somatic and thought problems as skin problems, vomit, stomach problems, sleep problems and unusual thoughts compared with healthy subjects and of emotional problems as anxiety, depressive withdrawal and somatic complaints.…”
Section: Discussionmentioning
confidence: 69%
“…Some studies showed a high prevalence of psychiatric morbidity among syncope patients, with rates up to 80% in adult patients, but relevant data in children and adolescents are few [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HypHantiS et al [153] reported an incidence of 35% in clinically significant depressive symptoms in children and adolescents with Neurocardiogenic Syncope, a 2.6-fold higher rate compared with healthy control subjects. Family functioning, as indicated by child-parent relationships and family cohesion, was associated with depressive symptomatology.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Several studies [153][154][155][156][157][158][159][160] in adults have shown that patients with syncope exhibit high levels of psychological distress, including anxiety and depression. HypHantiS et al [153] reported an incidence of 35% in clinically significant depressive symptoms in children and adolescents with Neurocardiogenic Syncope, a 2.6-fold higher rate compared with healthy control subjects.…”
Section: Comorbiditiesmentioning
confidence: 99%